Terminal differentiation into adipocyte and growth inhibition by PPARγ activation in human A549 lung adenocarcinoma cells. Issue 6 (1st November 2020) - Kim, Dae-Young; Moon, Sun-Ha; Han, Jang-Ho; Kim, Mi-Jeong; Oh, Seong-Ju; Bharti, Dinesh; Lee, Sung-Ho; Park, Jong-Kuen; Rho, Gyu-Jin; Jeon, Byeong-Gyun
ABSTRACT: The present study investigated the terminal differentiation capacity into adipocytes and subsequent growth inhibition in A549 cancer cells treated with pioglitazone (PGZ), a PPARγ activator. The rate of cell growth in A549 cells was significantly ( P  < .05) inhibited in concentrations above 10 μM PGZ while maintaining less cytotoxic effects in MRC-5 fibroblasts. Following 50 μM PGZ treatment, population doubling time (PDT) was significantly ( P  < .05) increased by inhibition of cell growth, as per increasing PGZ exposure time by up to 4 weeks. The adiposome-like vesicles were commonly observed in the PGZ-treated A549 cells, and the vesicles were highly stained with Oil-Red O solution. In addition, the cell size and expression of GLUT4 and PPARγ were significantly ( P  < .05) increased, as per increasing PGZ exposure time by up to 4 weeks. The significant ( P  < .05) down-regulation of telomerase activity and up-regulation of senescence-associated β-galactosidase (SA β-GAL) activity was displayed in the PGZ-treated A549 cells, as per increasing PGZ exposure time by up to 4 weeks. The G1 phase of the cell cycle was also significantly ( P  < .05) increased in the PGZ-treated A549 cells compared with untreated A549 cells. The present results have demonstrated that activation of PPARγ using PGZ induces cellular differentiation into adipocytes and inhibits cell growth in the A549 cancer cells. The terminal differentiation into adipocytes could offer potent chemotherapy in the cancer cells showing high glucose metabolism.